1997
DOI: 10.1023/a:1018509231331
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The paper describes molecular dynamics (MD) simulations on the crystal structures of the Ibeta and II phases of cellulose. Structural proposals for each of these were made in the 1970s on the basis of X-ray diffraction data. However, due to the limited resolution of these data some controversies remained and details on hydrogen bonding could not be directly obtained. In contrast to structure factor amplitudes in X-ray diffraction, energies, as obtained from MD simulations, are very sensitive to the positions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
3
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(139 citation statements)
references
References 6 publications
8
125
3
3
Order By: Relevance
“…The flask was immersed in an oil bath, the pressure was reduced (2 mm Hg) and the oil bath temperature was heated from room temperature to 110 °C at 3 °C/min. The oil bath temperature was externally controlled (FE50RP controller, Flyever, The cellulose I chains has a higher mobility, when swelled by NaOH, allowing them to rotate about their axes, producing the antiparallel structure, characteristic of cellulose II [19] . This change is due to the fact that the hydroxymethyl group (-CH 2 OH) can assumes different conformations, generating two different packing structures of cellulose chains in a microcrystal.…”
Section: Dissolution Of the Mercerized Linters Cellulosementioning
confidence: 99%
See 2 more Smart Citations
“…The flask was immersed in an oil bath, the pressure was reduced (2 mm Hg) and the oil bath temperature was heated from room temperature to 110 °C at 3 °C/min. The oil bath temperature was externally controlled (FE50RP controller, Flyever, The cellulose I chains has a higher mobility, when swelled by NaOH, allowing them to rotate about their axes, producing the antiparallel structure, characteristic of cellulose II [19] . This change is due to the fact that the hydroxymethyl group (-CH 2 OH) can assumes different conformations, generating two different packing structures of cellulose chains in a microcrystal.…”
Section: Dissolution Of the Mercerized Linters Cellulosementioning
confidence: 99%
“…The parallel chain structure, characteristic of cellulose I, occurs when the -adjacent chains have the CH 2 OH groups in the same conformation. The antiparallel structure, characteristic of cellulose II, occurs when the adjacent chains have the -CH 2 OH groups in different positions [11,19] .…”
Section: Dissolution Of the Mercerized Linters Cellulosementioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that the crystalline type of the fiber tended to vary from cellulose I structure to cellulose II structure when it was treated using the two-step chemical treatment. According to studies by Kroon-Batenburg and Kroon (1997) and Zugenmaier (2001), the crystalline type of the cellulose II structure was rather active, and its crystallites' sizes were rather larger than those of cellulose I structure, which meant accessibility to a solvent for the fiber was superior with a cellulose II structure. As a result, the absorbability of the fluff pulp fiber was increased when using a two-step chemical treatment.…”
Section: Effect Of Two-step Chemical Treatment On the Fiber Crystallimentioning
confidence: 99%
“…The formation of cellulose fibers constitutes approximately 30 entities of cellulose molecules in each subunit assembled to produce large units known as microfibrils. Ultimately, these micro-fibrils assemble to make long cellulose fibers (Koyama et al 1997;Kroon-Batenburg and Kroon 1997).…”
Section: Introductionmentioning
confidence: 99%